2005
DOI: 10.1590/s1678-77572005000100014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of chemical composition of packable resin composites by scanning electron microscopy

Abstract: RESUMO COMPARISON OF CHEMICAL COMPOSITION OF PACKABLE RESIN COMPOSITES BY SCANNING ELECTRON MICROSCOPYCOMPARAÇÃO). Methods and Materials: the specimens measured 4mm in diameter and 4mm in thickness. Five specimens were made for each shade of the materials. They were light cured for 40 seconds at a power of 600mW/cm². Subsequently, the specimens were removed from the plates and ground to powder and then pressed into holes measuring 4mm in diameter in a Teflon matrix, using the plates of the same material as bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…Di Francescantonio et al () analyzed the chemical elements and morphology of filler particles of four resins and found large amounts of silicon and other inorganic elements, such as aluminum, fluoride, barium, and zirconia in all samples. Silva, Veeck, Oliveira, and Souza () found that the chemical compositions of four different shades of two bulk fill composites was practically the same and included carbon, oxygen, aluminum, silicon, fluoride, and barium, similar to the present study.…”
Section: Discussionsupporting
confidence: 88%
“…Di Francescantonio et al () analyzed the chemical elements and morphology of filler particles of four resins and found large amounts of silicon and other inorganic elements, such as aluminum, fluoride, barium, and zirconia in all samples. Silva, Veeck, Oliveira, and Souza () found that the chemical compositions of four different shades of two bulk fill composites was practically the same and included carbon, oxygen, aluminum, silicon, fluoride, and barium, similar to the present study.…”
Section: Discussionsupporting
confidence: 88%
“…A difference of 18% was observed when comparing third-generation LEDs and of almost 35% when comparing VALO and Emitter A Fit equipment. More detailed information regarding the material’s composition must be provided by the manufacturer to explain this result since the shade can change the RBC composition [ 26 ].…”
Section: Discussionmentioning
confidence: 99%